2020
DOI: 10.1016/j.bja.2020.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium: perioperative assessment, risk reduction, and management

Abstract: Postoperative delirium is a relatively common and serious complication. It increases hospital stay by 2e3 days and is associated with a 30-day mortality of 7e10%. It is most prevalent in older patients, those with existing neurocognitive disorders, and those undergoing complex or emergency procedures. Preclinical and clinical research in recent years has uncovered more about the pathophysiology of postoperative delirium and may yield more potential therapeutic options. Using the enhanced recovery pathway frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
263
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(320 citation statements)
references
References 150 publications
9
263
1
4
Order By: Relevance
“…Morbidity of POD is 19.6% in the control group, which was consistent with L.Evered's result [13] (15-53%), and it occurred mainly in the rst three days [34] due to the effects of anxiety, pain [35] , and residual anesthetic. However, there was no signi cant statistical difference in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Morbidity of POD is 19.6% in the control group, which was consistent with L.Evered's result [13] (15-53%), and it occurred mainly in the rst three days [34] due to the effects of anxiety, pain [35] , and residual anesthetic. However, there was no signi cant statistical difference in this study.…”
Section: Discussionsupporting
confidence: 87%
“…[ 8 , 9 ] Postoperative delirium can exacerbate the condition and increase the risk of pulmonary infections, electrolyte disturbances, deep vein thrombosis, and falls, thus prolonging the length of hospital stay, increasing the cost, and burdens of patients and society. [ 10 , 11 ] It is been reported that the mortality of patients with delirium after hip fracture surgery increased by about 3 times compared with patients without delirium in 6 months after surgery. [ 12 ] Therefore, the management of delirium after hip fracture surgery is essential to the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although still elusive, the underlying factors in the pathogenesis of POD appear to be numerous. Patient age and gender, preexisting cognitive decline, comorbidities including (among numerous others) alcohol abuse, diabetes, and hypertension, and emergency surgery were identified as predisposing factors that might not or at least might not be significantly influenced [ 1 ]. In contrast, precipitating factors such as perioperative pharmacological and anesthesiological management, extent and invasiveness of surgical measures, and preservation of fluid and temperature homeostasis can be actively controlled, thereby offering the chance to reduce the risk for POD development.…”
Section: Discussionmentioning
confidence: 99%
“…Since the prevalence of POD is known to increase with patient age, and the average age of the general surgical patient population likewise increases, so does the incidence of POD. Comorbidities and the type of surgery do have a further impact, resulting in a statistical risk for POD ranging from 2.5% in the general surgical population up to 70% in patients requiring emergency femur fracture repair [ 1 ]. POD is characterized as cognitive impairment with an acute and fluctuating disturbance in awareness and attention, appearing in either hyper- or hypoactive manifestation or a combination of both [ 2 ].…”
Section: Introductionmentioning
confidence: 99%